STUDY ON COMBUSTION CHARACTERISTICS OF COAL-BIOMASS FOR CO-FIRING SYSTEM AS A FEEDSTOCK OF COAL GASIFICATION PROCESS - Datin Fatia Umar; Gandhi Kurnia Hudaya; Fahmi Sulistyohadi (Puslitbang tekMIRA, 2017)
Biomass co-firing is recognised as a crucial technology to aid in the use of fossil fuels, particularly due to its relative ease of implementation. Many studies of the combustion processes associated with co-firing have been conducted elsewhere. This paper discusses the combustion characteristics of coal and torrefied biomasses. Combustion profiles can be used to study certain combustion properties of fuels and fuel blends. The biomass fuels utilized in this study include twig, trunk and weed as the wastes from tea plantation. The results of this work provide data concerning the combustion processes of co-firing determined by simultaneous thermal analysis (STA) methods. Simultaneous thermogravimetric & differential scanning calorimetry/differential thermal analysis (STA, TGA-DSC/DTA) measures both the heat flow (DSC) and the weight changes (TG) in a material as a function of temperature or time in a controlled atmosphere. The results indicate that the mixture of coal and torrefied trunk in the weight ratio of coal-trunk of 25:75 shows the best combustion performance compared to other compositions of coal – torrefied biomass.